The Role of Diabetes Type I in Intervertebral Disc Degeneration. Issue 1 (April 2016) - Russo, Fabrizio; Vadalà, Gianluca; Ngo, Kevin; Fan, Yong; Trucco, Massimo; Sowa, Gwendolyn A.; Kang, James D.; Vo, Nam; Denaro, Vincenzo
Introduction: Diabetes Mellitus (DM) affects 25.8 million people of all ages. Previous studies suggest a link between DM and several connective tissue pathologies including those of cartilage and bone, however the role of DM in intervertebral disc degeneration (IDD) is unclear. The goal of this study was to measure disc degenerative changes in a murine model of human type I diabetes to establish the contributive role of DM in IDD. Material and Methods: Intervertebral discs (IVDs) were obtained from spines of Wt (C57Bl/6) mice and B6 Akita mouse model of type I DM. B6 Akita mice are hyperglycemic due to the Ins2Akita insulin mutation, which causes the insulin producing β cells to undergo apoptosis. Total disc proteoglycan (PG) content was measured by DMMB assay and safranin O/fast green histology. Glut1, a major glucose transporter in discs, was measured by quantitative RT-PCR, and cell death was assessed by TUNEL assay. Results: DMMB assay and Safranin-O staining both showed decreased disc GAG content in diabetic B6 Akita mice compared with that in age-matched nondiabetic Wt controls. Discs of B6 Akita mice also exhibited decreased level ( 5 fold) of Glut1 mRNA and increased level of TUNEL-positive cells. Conclusion: IVDs of diabetic B6 Akita mice exhibit an overall decrease in PG content and increased cell death. These changes correlate with a decrease in Glut1 gene expression. Experiments are being done to evaluate that increased cell death in the IVDs of B6 Akita mice is a result of diminished glucose uptake (decreased Glut1) in disc tissue. These diabetic mice may represent a useful model to explore the mechanism of how diabetes affects IDD through its impacts on glucose metabolism in disc tissue.